Behavioral Finance Explanation of Retail Investors’ Approach to Portfolio Design - V. V. Kolmakov; A. G. Polyakova; S. V. Polyakov (Финансы: теория и практика)
The digital space facilitates individuals’ access not only to securities, but also to information that can influence their decisions. When making decisions about selecting securities to include in an investment portfolio, individual investors strive for rationality, but are influenced by various behavioral factors that increase as the digital space expands. We assume that, in addition to profitability and risk, decisions about selecting securities for investment are influenced by various behavioral factors, fundamentally shaped by motives of thrift and caution in combination with fear of missing out (FOMO) and other phenomena described in the theory of behavioral finance. We test an approach that allows us to assess, without resorting to sociological tools, the degree of significance and potential influence on the choice of a retail investor of such parameters as the affordability and liquidity of securities. Our approach is to design a profitability and risk ranking of securities included in the MOEX40 index, and to incrementally adjust the ranking by affordability and liquidity in indicators various combinations. An instrument’s rank change compared to the base ranking is a measure of the factor significance from the point of view of a quasi-rational retail investor. We have empirically shown that relatively more expensive lots are prone to more significant decrease of investment appeal that in some cases cannot be compensated by higher returns. The developed framework can be used by portfolio managers and issuers to assess the potential demand for securities by retail investors, to explain and predict their antipathy to relatively more expensive instruments. The result of the study can also serve as a theoretical justification for splitting expensive shares in order to increase their attractiveness for retail investors.